Gangguan Psikotik Akut Dan Gangguan Skizoafektif - Mila Astari Harahap; Desy Dita Nelvia (Jurnal Ventilator, 2023)
Acute psychotic disorder is a mental disorder characterized by the onset of one or more symptoms, among which the symptoms are delusions, hallucinations, bizarre postures and behavior, and disorganized speech. The diagnosis of acute psychotic disorder was established based on the Diagnostic and Statistical Manual of Mental Disorders 5 (DSM-5) criteria. It is generally considered rare, as one study of military recruits found in which the estimated DSM-III-R incidence of brief reactive psychosis was 1.4 per 100,000 recruits. Schizoaffective is a mental disorder characterized by two recurrent features, namely schizophrenia (meets criterion A for schizophrenia) and mood episodes, both major depression and bipolar. Schizoaffective disorder, occurs in 0.2% of the general population in America, 9% of people with schizoaffective hospitalization.